A review of water injection applied on the internal combustion engine. (15th March 2019) - Zhu, Sipeng; Hu, Bo; Akehurst, Sam; Copeland, Colin; Lewis, Andrew; Yuan, Hao; Kennedy, Ian; Bernards, Johan; Branney, Ciaran
Highlights: A comprehensive review of water injection applied on the internal combustion engine was conducted. Different implementations of water injection were introduced and compared. Mechanisms of the in-cylinder combustion process with water addition were discussed. Comparisons and combinations of water injection with other techniques were summarized. Abstract: As a promising technique to reduce the in-cylinder temperature and exhaust temperature, mitigate combustion knock, improve combustion phasing and decrease NOx emissions, water injection applied on different types of engines has attracted extensive attention in recent years to further improve fuel economy and fulfill stricter emission regulations. Since mechanisms of water injection with different aims are distinct, benefits on engine performances and emissions are also varied. This paper intends to give a comprehensive review of water injection applied on the internal combustion engine. First, different implementations of water injection are introduced, followed by a detailed description of water evaporation processes. Second, mechanisms of the in-cylinder combustion process with water addition are discussed with respect to the heat release rate, knock tendency and emission formations. Next, recent works of water injection applied on different kinds of engines are reviewed with special attentions given to the comparisons of different implementations and injection parameters. Furthermore, comparisons and combinations of water injection with other advanced engine techniques are summarized. Finally, critical issues of current research on the water injection technique are discussed.